Prospect and challenges of land development: challenges of the Malaysian torrens system in the 21st century - Mohamad, Nor Asiah; Mubarak Ali, Bashiran Begum (2007)
Torrens system was introduced to provide certainty and accuracy of title and to avoid any legal problems of dual dealings. One of the earliest land registration codes was the Selangor Registration of Titles 1891. Section 4 of the Code, had applied a strict rule of registration of rigid application of registration whereby any land transactions that had to be registered shall be declared null and void. The provision had been repealed. Even though the courts have themselves to closely interpret the law according to the intention of the legislature but differences of opinion still occur and in many instances the law has been constructively interpreted by the court. This is due to the vast land development and the frequent changes in the land policy. The objective of this paper is to analyse certain areas in land law that poses challenges to a healthy development of the dynamic Malaysian land system. The latest judgement, for example, on the effect of registration of title which gave rise to the immediate indefeasibility of title in Adorna Properties v Boonsom Boonyanit2 has been received with mixed views and unwelcome comments. By virtue of that, other issues have appeared and need serious attention; such as security of land title, the insurance policy for land. the right pf the bona fide purchaser, the position of notice of any earlier interest and also the encroachment of equitable rights and interest under the Malaysian land tenure. Moreover, in the era of globalization and computerization, there is always a question for all the land owners as to what extent the government is seriously looking into these problems. How prepared is the government in facing all these future challenges strategically, physically, and financially.